An Immersive Musical Exploration of Nature in Virtual Reality Environment - Dokic, Mirjana (Asian Journal of Media and Communication, 2024)
Rapid ecological, cultural and social changes pose huge problems for humanity since they represent a great danger to the future of the planet Earth. These current transformations encourage art-science research which has proven to be a valuable means for communication of such challenges. Creative media artists effectively address and critically discuss the impact of cultural and social changes on environment. In the field of virtual heritage, they combine virtual reality and cultural and natural heritage offering an opportunity for the audience to become an integral part of the immersive heritage experiences. This conceptual article offers theoretical reflections on the role of hybrid audiovisual media, as a fusion of virtual reality, music and soundscape, in communicating the importance of natural heritage protection. Conceptual framework of this research combines concepts from new media theory and theory of musical emotions including BRECVEMA framework. Following new media theory, with aim to communicate meaning, this project includes creation of the Virtual Heritage Exhibition, representing natural heritage of Hong Kong, and in particular Hong Kong UNESCO Global Geopark and Indo-Pacific Humpback Dolphin. Musical content and semiotics are in the form of sonification, while visual semiotics are audio-reactive visual effects applied to the natural landmarks in the virtual reality 360 videos. To evaluate if the goal of creating audio-visual virtual heritage environment that allows intercultural communication and learning for the audience is achieved, user experience evaluation is based on the concepts of and theory of musical emotions including BRECVEMA framework.